2012
DOI: 10.6061/clinics/2012(03)09
|View full text |Cite
|
Sign up to set email alerts
|

Isolated total RNA and protein are preserved after thawing for more than twenty-four hours

Abstract: OBJECTIVE: The preservation of biological samples at a low temperature is important for later biochemical and/or histological analyses. However, the molecular viability of thawed samples has not been studied sufficiently in depth. The present study was undertaken to evaluate the viability of intact tissues, tissue homogenates, and isolated total RNA after defrosting for more than twenty-four hours.METHODS:The molecular viability of the thawed samples (n = 82) was assessed using the A260/A280 ratio, the RNA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Gene expression was assessed via RT-PCR as previously described (28). The primers used for the RT-PCR are included in Supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression was assessed via RT-PCR as previously described (28). The primers used for the RT-PCR are included in Supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…However, this result may not be universally applied to other analyses of muscle samples, such as western blotting and enzyme activity assays, as well as to all mishandling actions. For example, the manipulations we performed with the muscle samples took place over only a short time-span, and it has been reported that RNA is not viable in tissues that have been defrosted for more than 24 hours [ 21 ]. Thus, despite our results, researchers should still be cautious with sample acquisition and handling (see our recommendations in Box 1 ).…”
Section: Step 3: Rna Assessmentmentioning
confidence: 99%
“…It has previously been reported that isolated total RNA is preserved after thawing for 24 hours at room temperature (e.g., in the case of freezer breakdown) [ 21 ]. We also introduced other inadvisable actions that could potentially introduce RNase to the sample, but these failed to degrade the RNA samples.…”
Section: Step 3: Rna Assessmentmentioning
confidence: 99%
“…The gene expression was assessed via RT-PCR as previously described (28). The primers used for RT-PCR are included in Table 1.…”
Section: Rna Isolation and Gene Expression Of Ras Components In Both mentioning
confidence: 99%